SUPERVISI KEPALA SEKOLAH BERBASIS COACHING TIRTA DALAM MENINGKATKAN PROFESIONALISME KOMPETENSI GURU SD NEGERI - Yusnidar, Yusnidar; Rasyid, Suparta; Marisa, Riandi (Hijri, 2024)
The aim of this research is to find out 1) How the principal's supervision planning based on TIRTA coaching is to increase the professionalism of teacher competence; 2) How is the implementation of TIRTA coaching-based principal supervision in increasing teacher professionalism and competency; 3) What is the evaluation or follow-up of principal supervision based on TIRTA coaching in increasing teacher professionalism and competency? This research method uses qualitative with a descriptive approach. The place and time of the research was held at SDN 7 Baktiya and SDN 2 Lhoksukon and the time of the research was carried out in July - August 2024. Data collection techniques were observation, interviews and documentation. Meanwhile, data analysis techniques include reduction, display, and conclusion drawing/verification. The research results show that 1) a. Planning for academic supervision of the principal of Sdn 2 Lhoksukon is carried out through several aspects, namely 1) the aim is to assist in improving teacher professionalism, 2) the target of academic supervision carried out by the madrasah principal for all teachers or teaching staff 3) the stages of academic supervision by holding a meeting on the division of duties of the madrasah principal together with all the teachers, then create an academic supervision schedule, and finally, prepare a supervision instrument. 4) the academic supervision planning program is prepared at the beginning of the school year, while in the middle of the semester the head of the madrasah carries out academic supervision observations in class; 2) b. The implementation of Academic Supervision at SDN 2 Lhoksukon has gone well in accordance with existing provisions, including: a) class visits, the head of the madrasah has carried out class visits in accordance with the teacher's teaching schedule. b) classroom observation, the head of the madrasah makes careful observations, using certain instruments and running smoothly can help teachers who want to gain experience; 3) the results of the principal's academic supervision on the aspect of teacher activity in carrying out their duties have been carried out well, this can be seen from the supervision activities carried out by the principal which have had a good impact on building teacher discipline towards their duties.